Bioresources, biodiversity and eco-management - Kavita Sharma3, Mrs. Sheela Dubey1*, Dr M. Garg2 and Dr. (Journal of Experimental Sciences, 2011)
This paper introduces a special feature on biodiversity conservation and Bioresources Management. Bioresources are important components for progress and economic activities of a nation. Hence, bioresources management is very important for human welfare. Ecosystem management in a particular location is important and integral part for the conservation and protection of biological diversity. The conservation of biological diversity is a serious and common concern of human beings for better living. The conservation and sustainable use of biological diversity is of critical importance to meeting of food, fodder, fiber, health, water and other needs of growing world population.Ã‚Â  For the purpose, access to and sharing of both genetic resources and technologies are essential. Effort must be made to conserve biological diversity for the welfare of present and future generations.